Digital storytelling : a creator's guide to interactive entertainment - Miller, Carolyn Handler (Focal Press, Taylor & Francis Group, 2014)
"Digital Storytelling shows you how to create immersive, interactive narratives across a bevy of platforms, devices, and media. From age-old, storytelling techniques to cutting-edge development processes, this book covers creating stories for all forms of entertainment like social media, transmedia, games, apps, and second screen experiences. The way a story is told, a message is delivered, or a narrative is navigated has changed dramatically over the last few years. Stories are told through video games, interactive books, and social media. Stories are told on all sorts of different platforms and through all sorts of different devices. They're immersive, letting the reader interact with the story, letting the reader shape the story themselves. This book features case studies that cover a multitude of platforms and different story types. It also shows you how to plan processes for developing interactive narratives for all forms of entertainment and messaging: advertising, education, and interactive cinema. Digital Storytelling features interviews with some of the industry's biggest names, showing you how they build and tell their stories."--Resumé vydavatele
Terminologický slovník
Keywords: digitální vyprávění; interaktivní multimédia; zpracování dat; digital storytelling; interactive multimedia; data processing; příručky; handbooks and manuals